The impact of elevated CO2 on methanogen abundance and methane emissions in terrestrial ecosystems: A meta-analysis - Yiwen Ding; Mingyu Wang; Xiaojuan Du; Xue He; Tianle Xu; Xinyu Liu; Fuqiang Song (iScience)
Summary: Methane (CH4), one of the major greenhouse gases, plays a pivotal role in global climate change. Elevated CO2 concentration (eCO2) increases soil carbon storage, which may provide a valuable material base for soil methanogenic microorganisms and stimulating their growth, thereby ultimately affecting CH4 emissions. Therefore, to comprehend the effect of eCO2 on CH4 emissions, we conducted a meta-analysis encompassing 398 datasets from 59 publications (total of 50 sample sites). The results show that eCO2 promotes both the abundance of the functional methanogenic gene mcrA and CH4 emissions. However, this enhancement is modulated by a range of factors, such as the eCO2 duration, land use types and soil texture, and there are significant interactions. This study offers new insights into the effects of eCO2 on CH4 emissions across diverse ecosystems and the underlying driving forces, vital for predicting the response of global terrestrial ecosystems in the face of future climate change.